Perbandingan Kejadian Missing String IUD CUT 380A Pascasalin antara yang Dipasang Menggunakan R_Inserter dengan yang Dipasang Menggunakan Klem Cincin (Evaluasi 13-24 Bulan) - Dewi, Silvy Kusuma; Siswosudarmo, Risanto; Lutfi, Muhammad (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2017)
Background: One of the main complaint of IUD client was missing string. The main cause of missing string was folded string into the cervical canal. The incidence of translocation in case of missing string was 0 – 5%.Objective: To compare the incidence of missing strings IUD CuT 380A inserted by R_inserter compared to ring forceps during postpartum period in addition to compare incidence of malposition, cumulative expulsion, the continuation of IUD, pregnancy and menstrual complaintsMethod: The study was conducted in Sardjito Hospital Yogyakarta. The subjects were divided into two groups, of exposed group (inserted postpartum IUD using R_inserter) and control group (inserted postpartum IUD by using ring forceps). Follow-up was performed in the period of 13-24 months postpartum. Data was analized with Chi-square test and relative risk for comparing two proportions.Result and Discussion: A total of 178 study subjects consisted of 91 subjects inserted with R_inserter and 87 subjects with a ring forceps. The incidence of missing strings in R_inserter was lower than ring forceps group, 1.2% vs. 3.6% (RR 0.33; 95% CI 0.36-3.18). There was only one subject IUD malposition from ring forceps group. The incidence of expulsion cumulative in the R_inserter was higher than ring forceps, 6.0% vs 4.1% (RR 1.47; 95% CI 0.43-5.05). The continuation rate of IUD in R_inserter and ring forceps groups was 83% and 85.7% (RR 0.97; 95% CI 0.86-1.09) and no incidence of pregnancy. Number of menstrual complaints on R_inserter were lower than the ring forcep 2.4% vs. 3.6% (RR 0.66%; 95% CI 0.11-3.83).Conclusions: There was no difference in the incidence of missing strings, malposition, expulsion, continuity and menstrual complaints between IUD CuT 380A inserted by R_inserter and ring forceps during the postpartum period.Keywords: postpartum IUD, R_inserter, ring forceps, missing strings, malposition.